Promoting Social Harmony Through Neo-Sufism-Based Religious Inclusivity - Muvid, Muhamad Basyrul Muvid; PS, Alaika M Bagus Kurnia; Alauddin, Muhammad Badat (LPPPM STAI Darul Hikmah Bangkalan, 2025)
Diversity is proof of God's power that must be accepted by all of creation. However, diversity becomes the embryo of division because of differences in vision, mission, and even beliefs, due to the absence of a common thread connecting one to another. Added to this is a textual understanding of religion that gives rise to religious fanaticism and exclusivism. This paper aims to find solutions to realize the harmonization of diversity in society through religious inclusiveness based on neo-Sufism. The research method used is a literature study with data collection techniques based on documents (articles, books, religious texts, electronic media) that support this theme, and data analysis techniques using induction and interpretation. The results show that with the neo-Sufism approach, a person's religious inclusion does not only stop at the mind (knowledge) but also reaches the heart (feelings), so that tolerance, empathy, compassion, mutual assistance, and social solidarity arise sincerely, selflessly, and without any interests. This inclusive attitude will not change when situations and conditions change. This means that neo-Sufism-based religious inclusiveness educates people to respect others (even if they are different) with sincere attention and compassion after going through Sufi spiritual processes and stages. This model can be practiced in real life when living side by side in diversity, in interfaith dialogue, working in heterogeneous places (religion, ethnicity, etc.), and also for government officials who are indeed servants of the people universally. This can be a recommendation to policymakers and community leaders to educate the public to be more moderate (inclusive) in their religious practices by making Sufi values a model in the midst of a diverse society